The role of clinical champions in facilitating the use of evidence-based practice in drug and alcohol and mental health settings: A systematic review - Wood, Katie; Giannopoulos, Vicki; Louie, Eva; Baillie, Andrew; Uribe, Gabriela; Lee, Kylie S; Haber, Paul S; Morley, Kirsten C (Implementation research and practice, 2020)
Background: The dissemination and adoption of research into clinical practice in health care settings is a complex and challenging process. Clinical champions have been increasingly used in health care to facilitate the implementation and adoption of evidence-based practice and to overcome organizational barriers. In relation to substance use and mental health disorders, translation of new evidence into practice is an ongoing challenge. The utilization of a clinical champion to motivate staff to implement evidence-based practice in these settings may improve treatment quality and reduce the burden of disease. We thus aimed to conduct a systematic review to examine the role and efficacy of clinical champions in the drug and alcohol and mental health settings. Methods: We conducted a systematic literature search (1980-present) using the following databases: PubMed and PsycINFO. Additional studies were identified using reference searches of relevant reviews. Results: Thirteen separate studies were included in the final review. Clinical champions were typically selected rather than emergent, including clinical staff members engaging in a professional clinical role (e.g., physicians, psychologists, social workers). Training provided for these roles was often not stated. Clinical champions assisted with faster initiation and persistence in the application of novel interventions, facilitating overcoming system barriers, and enhanced staff engagement and motivation. Conclusions: In the substance use and mental health field, clinical champions appear to be an important component to facilitating practice changes. Future studies should provide specific details regarding attributes and training and also examine the relevant combination of personal characteristics and training sufficient to facilitate implementation of evidence-based practice in drug and alcohol and mental health settings. Plain language abstract Treatment delivery in drug and alcohol and mental health settings may not always be based on best available evidence. Organizational context and individual factors are important in determining whether new practices will be adopted. Passive approaches such as websites or treatment manuals do not necessarily lead to change in practice. The clinical champion model has been shown to be effective in aiding implementation of evidence-based practice in health care settings. However, there is limited evidence evaluating its use in drug and alcohol and mental health settings. The current review aims to synthesize and evaluate the use of clinical champions in implementation research in drug and alcohol and mental health settings. We found that clinical champions were typically clinical staff members engaging in a professional clinical role. Training provided for these roles was often limited. Clinical champions may assist with faster initiation and persistence in the application of novel interventions, facilitating overcoming system barriers, and enhanced staff engagement and motivation.